2008
DOI: 10.1111/j.1439-0531.2007.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

CASA Assessment of Kinematic Parameters of Ram Spermatozoa and their Relationship to Migration Efficiency in Ruminant Cervical Mucus

Abstract: Sperm motility is an indicator of male fertility because of its importance for sperm migration through the female genital tract and for gamete interaction at fertilization. This study analyses the relationship between computer assisted semen analysis (CASA) motility patterns and sperm migration of rams in ruminant cervical mucus. In experiment 1, spermatozoa extended with sperm analysis medium (SAM) and seminal plasma were compared in terms of motility. In experiment 2, 56 semen samples were collected either w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 32 publications
(67 reference statements)
5
40
4
2
Order By: Relevance
“…The inconsistency between the CASA parameter values obtained in this study with those reported in the studies of Robayo et al (2008), Munyai (2012), and Palacín et al (2013) emphasizes the importance of standardizing CASA assessment protocols to allow for comparison of studies from different laboratories. Standardization would enable researchers to potentially correlate CASA results to the in vivo scenario of sperm transport in the female reproductive tract.…”
Section: Resultscontrasting
confidence: 82%
“…The inconsistency between the CASA parameter values obtained in this study with those reported in the studies of Robayo et al (2008), Munyai (2012), and Palacín et al (2013) emphasizes the importance of standardizing CASA assessment protocols to allow for comparison of studies from different laboratories. Standardization would enable researchers to potentially correlate CASA results to the in vivo scenario of sperm transport in the female reproductive tract.…”
Section: Resultscontrasting
confidence: 82%
“…The lack of a significant correlation between the ability of epididymal spermatozoa to penetrate cervical mucus and its kinematic motility parameters suggests that in the current study, the mucus-penetrating ability of spermatozoa was not influenced by its motility or velocity but rather by some unknown means conferred by exposure to seminal plasma. This contradicts published reports in the ram (Suttiyotin et al 1992, Robayo et al 2008) and human (Keel & Webster 1988), who linked increased mucus penetration with increased velocity and motility. However, in the latter study, 10-15% of patients with otherwise normal semen parameters demonstrated poor mucus-penetrating ability, suggesting that mucus penetration tests provide information about sperm function not attainable by motility analysis alone (Keel & Webster 1988).…”
Section: Cervicalcontrasting
confidence: 55%
“…Los iones de bicarbonato activan la cAMP, lo que ha llevado a la protein Kinase C a ser uno de los reguladores del movimiento espermático (Mortimer, 1997), y cambios en la composición o el pH del plasma seminal pueden ser la causa de las diferencias en motilidad individual. Robayo et al, (2008) indican que VCL y VAP se correlacionan de manera positiva con la habilidad de migrar en el moco cervical de la oveja, y VAP con la eficiencia de ésta migración, pero encontraron un efecto negativo entre el desplazamiento lateral de la cabeza y la migración.…”
Section: Los Estudios Existentes De Efectos Del H Rosa-sinensis Son unclassified